2017
DOI: 10.19090/pp.2017.1.37-61
|View full text |Cite
|
Sign up to set email alerts
|

Serbian Adaptation of the Brand Personality Scale (Bps): an Application to Tourism Destinations

Abstract: The main aim of this research was to validate a Serbian adaptation of the Brand Personality Scale (BPS: Aaker, 1997) while applying it to tourist destinations. The BPS was developed as a measure of five personality traits of any kind of brand: Sincerity, Excitement, Competence, Sophistication, and Ruggedness. In the first study that was carried out on 192 (76% female) tourists from student population, exploratory factor analysis of the BPS resulted in a four-factor structure: Competence, Excitement, Sophistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Even though the original model of brand personality indicated that five dimensions are independent and uncorrelated (Aaker's, 1997), previous results showed that these dimensions are related (Jovanović, 2014;Jovanović et al, 2017;Murphy et al, 2009). In the final DPS model, correlations between dimensions are low to moderate, indicating that although some dimensions shared similarities, the distinction between them could be made.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…Even though the original model of brand personality indicated that five dimensions are independent and uncorrelated (Aaker's, 1997), previous results showed that these dimensions are related (Jovanović, 2014;Jovanović et al, 2017;Murphy et al, 2009). In the final DPS model, correlations between dimensions are low to moderate, indicating that although some dimensions shared similarities, the distinction between them could be made.…”
Section: Discussionmentioning
confidence: 81%
“…In the BPS, Ruggedness destination trait is described as rugged, tough, masculine, western, and outdoorsy. Ruggedness from BPS was shown to be inadequate in describing the personality of a travel destination in a previous study (Jovanović, 2014;Jovanović et al, 2017;Papadimitrou et al, 2014;Usakli & Baloglu, 2011). For example, items rugged, tough, and western are difficult to associate with a travel destination (Jovanović, 2014;Jovanović et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations